A high-mass Q-TOF for the analysis of protein complexes - Sobott, F; McCammon, MG; Hernández, H; Robinson, C (2002)
A tandem mass spectrometer (a modified Q-TOF) for the analysis of protein complexes was discussed. With nanoflow-ESI, large biomolecular assemblies were amenable to MS analysis in native environments. Using the instrument, complexes of the bacterial GroEL chaperonin were detected as intact molecular ions around m/z 12,000-14,000. It was found that isolation of single, well-resolved charge states and subsequent collision-induced dissociation (CID) leads to the formation of ions from individual subunits and subcomplexes.